FRI0111 Body mass index (BMI) is not a surrogate of rheumatoid cachexia. (23rd January 2014) - Souffir, C.; Breban, S.; Neveu, S.; Paternotte, S.; Kolta, S.; Dougados, M.; Roux, C.; Briot, K.
Abstract : Background: Rheumatoid cachexia (RC) is a metabolic abnormality defined by a low fat-free mass with a normal or high fat mass in patients with Rheumatoid Arthritis (RA). It is predictor of poor health outcomes in RA. Objectives: The objectives of this study were to determine the prevalence of rheumatoid cachexia and its determinants in RA patients, and, during a 6-year retrolective follow-up, the body composition changes and its determinants. Data were compared with those of the body mass index (BMI, kg/m²). Methods: 133 patients with RA (115 women and 18 men) with a mean age 56.9±12.7 years, who consulted in a tertiary Department of Rheumatology were included; 91 of the patients (75 women and 16 men) were retrolectively followed during 6.3±2.0 years. Demographic data, disease duration, RA activity and severity, RA therapies were collected. Dual Energy X ray Absorptiometry (DXA) was performed for body composition measurement (fat free and fat mass index). We defined RC as fat-free mass index below the 10 th percentile together with fat mass index above the 25 th percentile (1 ). Results: 106(76.7%), 66(49.6%) and 86(64.7%) of the 133 patients were treated by DMARDs, corticosteroids and biological therapies, respectively at the time of the body composition assessment. Prevalence of rheumatoid cachexia was 45.1% (n=60), higher in men (66.7%) than in women (41.7%) (p=0.048). None of the patients with body mass index (BMI) below 19kg/m 2 had RC while prevalence of RC was high (82.4%) in overweight patients (25<BMI≤30). Univariate analysis showed that disease duration and activity disease, use of biological treatments and corticosteroids were not associated with presence of RC. In the retrolective follow-up, 55 patients (59.8%) received continuously biological therapies, 27 (29.3%) intermittently and 9 never received biological therapies. BMI significantly decreased over follow-up (2.8% (±10.3), (p= 0.005). Fat mass index significantly increased from baseline of 7.5% (±21.3) (p= 0.001) in whole population, in patients with continuous biological treatments (8.0 % (±20.4), p=0.005) and a trend was observed in patients without biological treatment (13.1% ±14.3, p=0.055) without any difference between groups. Fat free mass index did not significantly change from baseline. Body composition changes during the retrolective follow-up did not significantly change prevalence of RC. Conclusions: This study suggests that rheumatoid cachexia is frequent in RA patients even treated with biological therapies. Fat mass increase in RA can be observed in patients with biological therapies or without. In RA, Body Mass Index (BMI) cannot be used to identify patients with rheumatoid cachexia. References: Elkan AC, et al. Rheumatoid cachexia, central obesity and malnutrition in patients with low-active rheumatoid arthritis: feasibility of anthropometry, Mini Nutritional Assessment and body composition techniques. Eur J Nutr 2009; 48:315-22. Disclosure of Interest: None Declared